The bottleneck problem in large scale IEEE 802.15.4/ZigBee networks. (2017) - Chao, Chih-Min; Wang, Hsin-Hsiang
In this paper, we handle the bottleneck problem of ZigBee-based networks. The bottleneck problem occurs at the nodes near the ZigBee coordinator since they have too many data to deliver during the data gathering process. This is a fundamental problem which reduces network throughput and prolongs transmission delay. A possible solution is to schedule each node's transmission/receiving time properly. Two fundamental problems we have to answer for such scheduling are when and how long a node should keep awake to transmit/receive packets. To achieve efficient scheduling, in this paper, we propose a centralised top-down-maximum-load-first (TDMLF) scheme which utilises the contention-free guaranteed time slots (GTS) defined in IEEE 802.15.4. By increasing the number of concurrent transmissions, the proposed scheme achieves high system utilisation and thus alleviates the bottleneck problem. Through simulation and real system implementation, we verify that TDMLF successfully reduces the negative effects caused by the bottleneck problem.